Propranolol in Treatment of Huge and Complicated Infantile Hemangiomas in Egyptian Children - Basheir A. Hassan; Khalid S. Shreef (Hindawi Limited, 2014)
Background. Infantile hemangiomas (IHs) are the most common benign tumours of infancy. Propranolol has recently been reported to be a highly effective treatment for IHs. This study aimed to evaluate the efficacy and side effects of propranolol for treatment of complicated cases of IHs. Patients and Methods. This prospective clinical study included 30 children with huge or complicated IHs; their ages ranged from 2 months to 1 year. They were treated by oral propranolol. Treatment outcomes were clinically evaluated. Results. Superficial cutaneous hemangiomas began to respond to propranolol therapy within one to two weeks after the onset of treatment. The mean treatment period that was needed for the occurrence of complete resolution was 9.4 months. Treatment with propranolol was well tolerated and had few side effects. No rebound growth of the tumors was noted when propranolol dosing stopped except in one case. Conclusion. Propranolol is a promising treatment for IHs without obvious side effects. However, further studies with longer follow-up periods are needed.